Pengaruh Gaya Kepemimpinan Situasional dan Iklim Organisasi terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening (Studi Pada PT. Bank Kalteng Cabang Puruk Cahu) - Roy Romadhony Ampitrian Noor; Hairudinor Hairudinor; Irwansyah Irwansyah (Universitas Lambung Mangkurat, 2019)
This study aims to analyze the influence of situational leadership style variables (X1), organizational climate (X2), on employee performance (Y) with job satisfaction (X3) as intervening variable at PT. Bank Kalteng Branch Puruk Cahu. The number of samples determined is as much as 32 respondents who are the entire population on the object of research. Measurement in questionnaires using Likert scale. Data analysis method used is path analysis.The results of testing on the hypothesis, indicating that the variables of leadership style situasional significant to job satisfaction with regression coefficient of 0.538. The organizational climate has an insignificant effect on job satisfaction with regression coefficient of 0.181. Situational leadership style significant effect on employee performance through job satisfaction with a value of 0.408. Organizational climate has an insignificant effect on employee performance through job satisfaction with a value of 0.137. Keywords: Situational Leadership Style, Organizational Climate, Job Satisfaction, Employee Performance